Nitrogen Fertilization of No-Tillage Winter Cereals in the South-Central Region of Paraná, Brazil - Fontoura,Sandra Mara Vieira (2017)
ABSTRACT High winter cereal yields depend on an adequate supply of nitrogen (N). We developed a system for indicating N rates for wheat and barley in the South-Central region of the state of Paraná, Brazil, using results of 72 field experiments conducted from 2007 to 2012. The N rates recommended for winter cereals were estimated to supply the amounts of N fertilizer needed to obtain increasing yields (<3.5, 3.5-4.5, 4.5-5.5, and >5.5 Mg ha-1) of crops grown after soybean and corn on soils with a variable organic matter content (<40, 40-60, and >60 g dm-3). The apparent mineralization rate of soil N was estimated to be 1 % and the N fertilization efficiency 50 %. The N rates recommended for wheat ranged from 30 to 150 kg ha-1 when cultivated after soybean, and from 30 to 170 kg ha-1 after corn. The N rates for barley ranged from 30 to 120 kg ha-1 when grown after soybean, and from 30 to 130 kg ha-1 after corn. These N rates are consistent with those indicated by the Soil Fertility Commission for the states of Rio Grande do Sul and Santa Catarina (CQFS-RS/SC, 2016), and also with the rates of maximum economic efficiency estimated in our study. The proposed N rate recommendation system can be used by agricultural technicians and producers to manage N fertilization of wheat and barley in the South-Central region of Paraná, Brazil.